Banking in Asia : acquiring a profit mindset - Bowers, Tab; Gibb, Greg; Wong, Jeffrey (Singapore : John Wiley and Sons (Asia), 2003)
Business
2004-10-13
Keywords: Banking; Geographic markets; Corporate banking; Mergers; Asia